2008
DOI: 10.1159/000155223
|View full text |Cite
|
Sign up to set email alerts
|

Role of MIF in Inflammation and Tumorigenesis

Abstract: MIF has been described as a protein that plays an essential role in both innate and acquired immunity. Previous studies have demonstrated that MIF activates lymphocytes, granulocytes and monocytes/macrophages. Furthermore, MIF can counteract the physiological function of steroids, thus playing a role in immune system regulation. Further evidence for a role of MIF in immunity was obtained in mouse models of autoimmune disorders, where the inhibition of MIF resulted in a more benign disease progression. This obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
101
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 116 publications
1
101
1
2
Order By: Relevance
“…MIF has since been shown to be constitutively expressed in numerous tissues and cell types (30) and have a variety of biological activities, including pivotal roles in the regulation of immune and inflammatory responses and promotion of tumorigenesis (31). Elevated levels of MIF have been observed in a number of disease states including cardiovascular disease (32), arthritis (33), diabetes (34), sepsis (35), and many cancer types (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…MIF has since been shown to be constitutively expressed in numerous tissues and cell types (30) and have a variety of biological activities, including pivotal roles in the regulation of immune and inflammatory responses and promotion of tumorigenesis (31). Elevated levels of MIF have been observed in a number of disease states including cardiovascular disease (32), arthritis (33), diabetes (34), sepsis (35), and many cancer types (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its discovery in the mid-1960s as a T-cell-derived factor that modulated the motility of monocytes, macrophage migration inhibitory factor (MIF) has been shown to be involved in cancers [9][10][11][12][13]. Interestingly, both circulating and intracellular levels of MIF were elevated in patients with cancers, and the levels of MIF were closely correlated with tumor aggressiveness and metastatic potential, suggesting that MIF contributed to disease severity and survival [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, necessary to explore and investigate the tumorigenesis of gastric cancer and its novel therapy targets [6] . Macrophage migration inhibitory factor (MIF) is a multi-functional cytokine, which is associated with inflammation and tumorigenesis [7,8] . Recent studies have shown that MIF is related to the initiation and progression of gastric cancer, but its underlying mechanism is not very clear [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%